Temporal Reduction in COVID-19-Associated Fatality Among Kidney Transplant Recipients: The Brazilian COVID-19 Registry Cohort Study - Sandes-Freitas, Tainá Veras de (2022)
Data from the general population suggest that fatality rates declined during the course of the pandemic. This analysis, using data extracted from the Brazilian Kidney Transplant COVID-19 Registry, seeks to determine fatality rates over time since the index case on March 3rd, 2020. Data from hospitalized patients with RT-PCR positive SARS-CoV-2 infection from March to August 2020 (35 sites, 878 patients) were compared using trend tests according to quartiles (Q1: <72 days; Q2: 72–104 days; Q3: 105–140 days; Q4: >140 days after the index case). The 28-day fatality decreased from 29.5% (Q1) to 18.8% (Q4) (pfor-trend = 0.004). In multivariable analysis, patients diagnosed in Q4 showed a 35% reduced risk of death. The trend of reducing fatality was associated with a lower number of comorbidities (20.7–10.6%, pfor-trend = 0.002), younger age (55–53 years, pfor-trend = 0.062), and better baseline renal function (43.6–47.7 ml/min/1.73 m2, pfor-trend = 0.060), and were confirmed by multivariable analysis. The proportion of patients presenting dyspnea (pfor-trend = 0.001) and hypoxemia (pfor-trend < 0.001) at diagnosis, and requiring intensive care was also found reduced (pfor-trend = 0.038). Despite possible confounding variables and time-dependent sampling differences, we conclude that COVID-19-associated fatality decreased over time. Differences in demographics, clinical presentation, and treatment options might be involved.